Analisis Minat Berwirausaha di Kalangan Siswa - Baktiningsih Baktiningsih; Yasir Arafat; Achmad Wahidy (Jurnal Administrasi Pendidikan, 2021)
This study aims to find out: (1) To describe entrepreneurial motivation in SMA Negeri 2 Prabumuih (2) To describe entrepreneurial creativity in SMA Negeri 2 Prabumuih (3) To describe the unyielding attitude of entrepreneurship in SMA Negeri 2 Prabumuih. The type of research that will be used is a qualitative descriptive method, the population was students at SMA Negeri 2 Prabumulih as many as 80 respondents, the instruments used were questionnaires and interviews. The result of the study that there is a relationship between motivation, creativity, and abstinence attitude, the implication of this research is to give an idea that motivation, creativity, unyielding attitude can provide a positive relationship because it can increase the entrepreneurial interest of students and increase pre-employment and entrepreneurship learning in school. The results showed that (1) Describe entrepreneurial motivation in SMA Negeri 2 Prabumuih is quite good 39%, well 27%, very good 14%. (2) Describe entrepreneurial creativity in SMA Negeri 2 Prabumuih is very good 49%, good 10%, good enough 21% and less good 20% (3) Describe the unyielding attitude of entrepreneurship at SMA Negeri 2 Prabumuih. Very good 48%, good 21%, pretty good 20%, less good 10%.